2021
DOI: 10.1093/fampra/cmab099
|View full text |Cite
|
Sign up to set email alerts
|

Online health information-seeking behaviour of patients attending a primary care clinic in Malaysia: a cross-sectional study

Abstract: Background The internet has become a common source of health information; however, little is known about online health information-seeking behaviour (HISB) among patients in low- and middle-income countries (LMICs). Objectives This study aimed to determine the prevalence of online health information-seeking and its associated factors among patients in primary care in Malaysia. We also examined the reasons for, and the sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Researchers investigated how Malaysian patients searched for health information online and found that the most popular search engines were Google and Yahoo, while the most common websites were Wikipedia and MyHealth. 54,56 Less than half of the participants (12% and 47% reported by Lim HM et al and Maon et al respectively) were found to consult online health information with their doctors. 54,56 There are thousands of medical websites, some provide up-to-date medical news and reliable health information and some do not.…”
Section: Discussionmentioning
confidence: 97%
“…Researchers investigated how Malaysian patients searched for health information online and found that the most popular search engines were Google and Yahoo, while the most common websites were Wikipedia and MyHealth. 54,56 Less than half of the participants (12% and 47% reported by Lim HM et al and Maon et al respectively) were found to consult online health information with their doctors. 54,56 There are thousands of medical websites, some provide up-to-date medical news and reliable health information and some do not.…”
Section: Discussionmentioning
confidence: 97%
“…As this study was part of a larger study, which looks at the online health information-seeking behaviour among patients in a primary care clinic, we have used the calculated sample size of 379 from the main study. 4 …”
Section: Methodsmentioning
confidence: 99%
“… 2 This change is also observed in low-middle income countries (LMICs); recent studies found that there is a rising prevalence of online health information-seeking and exposure in LMICs, including Malaysia. 3 5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online health information is often assessed via websites (including sites specific to patient information, blogs, and news media), online support groups, forums, and social media. 2 The online health information-seeking (OHIS) behaviour is common, with its prevalence ranging from 35-54% in low-and middle-income countries 3,4 to as high as 70-80% in high-income countries. 5,6 However, the evidence on the impact of OHIS on health outcomes has been conflicting.…”
Section: Introductionmentioning
confidence: 99%